038 Screening for anxiety and depression in epilepsy—preliminary findings. Issue 10 (24th September 2010) - Rampling, J; Jackson, J; Docker, J; Von Oertzen, T; Cock, H; Mitchell, A J; Agrawal, N
Abstract : Aims: Anxiety and depression are more common in people with epilepsy than the general population and are associated with poor quality of life. This study aims to study the performance of a short non-verbal screening tool (revised emotional thermometer (ET) tool) for these conditions which are under-identified and undertreated in the epileptic patient group. Methods: A total of 122 people (53% female, 66% White British, age range 16–89, mean 39.6) attending the epilepsy clinic at Atkinson Morley Neurosciences centre completed five screening tools for anxiety and depression (NDDI-E; MDI; BDI-II; HADS; Revised Emotional Thermometers). These scales were scored and for depression BDI-II, NDDI-E, MDI, HADS depression and ET were compared while for anxiety HADS -anxiety and ET were compared. Results: The preliminary results for screening of depression suggest that the revised ET is a potentially useful tool with 44% of patients responding with clinically significant scores. This is comparable to the BDI-II (43%) and NDDI-E (35%). The MDI identified 19% of cases fulfilling ICD-10 diagnostic criteria for depression. Based on this sensitivity of all the tools is comparable (NDDI-E 96%, BDI 96%, ET 83%, HADS 70%). In screening for anxiety, the proportion of patients scoring positive for anxiety from ET are comparable with HADS (53% vs 48%). Conclusions: Results so far suggest that a brief non-verbal screening instrument (revised ET tool) may be useful in screening for anxiety and depression in patients with epilepsy. Further analysis of data is required to assess the sensitivity and specificity of this instrument and its overall usefulness in this population.